2015
DOI: 10.1186/s12883-015-0390-5
|View full text |Cite
|
Sign up to set email alerts
|

Dose-specific effect of simvastatin on hypoxia-induced HIF-1α and BACE expression in Alzheimer’s disease cybrid cells

Abstract: BackgroundAlzheimer’s disease (AD) is associated with vascular risk factors; brain ischemia facilitates the pathogenesis of AD. Recent studies have suggested that the reduction of AD risk with statin was achieved by decreased amyloidogenic amyloid precursor protein.MethodsWe used mitochondrial transgenic neuronal cell (cybrid) models to investigate changes in the levels of intracellular hypoxia inducible factor 1α (HIF-1α) and β-site amyloid precursor protein cleaving enzyme (BACE) in the presence of simvastat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 31 publications
2
13
0
1
Order By: Relevance
“…Our study was designed as a short-term study lasting 2 weeks. In cells, simvastatin exposure leads to immediate dose-related effects [27] , and in our 2-week study, we observed clear effects with a 25% and 50% reduction in plasma and LDL cholesterol concentrations, respectively. In the study by Larsen et al [7] , participants took simvastatin for one year.…”
Section: Discussionsupporting
confidence: 65%
“…Our study was designed as a short-term study lasting 2 weeks. In cells, simvastatin exposure leads to immediate dose-related effects [27] , and in our 2-week study, we observed clear effects with a 25% and 50% reduction in plasma and LDL cholesterol concentrations, respectively. In the study by Larsen et al [7] , participants took simvastatin for one year.…”
Section: Discussionsupporting
confidence: 65%
“…In the current study, 30-day treatment with high-dose Simvastatin resulted in improved clinical outcomes and cognition in mice with Alzheimer's disease. Improvements in apoptosis and cognition were consistent with the results of a recent study, indicating that Simvastatin had regulatory effects on the expression of pathological factors associated with Alzheimer's disease, enabling it to achieve positive therapeutic outcome ( 55 57 ).…”
Section: Discussionsupporting
confidence: 88%
“… The isoprenoid effect has been attributed to intracellular levels of GGPP and FPP which exhibit opposing effects on cognition . The effect of statins on the isoprenoid levels seems to be dose‐dependent. Low doses of statins preferentially affected the isoprenoid synthesis in cell models , without change in intracellular cholesterol levels, which resulted in decreased Aβ production . The beneficial role of statins on cognition related to the isoprenoid levels has been suggested to be a result of preferentially lowering FPP levels . More specifically, a protective mechanism of statins against glutamate excitotoxicity has been shown to occur by diminishing FPP levels.…”
Section: Medications With Potential Effects On the Brain Cholesterolmentioning
confidence: 99%